(untitled) (Indian Journal of Animal Production and Management, 2013)
The present study was carried out to see the effect of different housing system on 24 non-pregnant healthy Chhotanagpuri ewes which were allocated equally to three different groups. Animals of group I were kept between the temperature range of 350C to 400C in intensive system in hot and humid condition, animals of group II were kept under intensive system between 200C-270C and animals of group III were kept under extensive system and served as control. The ewes allotted to different treatment groups were of nearly similar age and body weight. The physiological considerations like reproductive hormones LH, FSH and other important metabolic hormones like Cortisol plays vital role in regulating the reproductive efficiency. Therefore Plasma LH, plasma FSH and plasma Cortisol hormones concentration were estimated during the experimental period. The study revealed that the Plasma LH and plasma FSH concentration between different groups did not vary significantly (p<0.01) while plasma Cortisol hormone varied significantly (p<0.05) among the groups. All the three hormones varied significantly within group. The plasma LH level decreased from day 20 to 135 and started increasing significantly on expected day of parturition and reached its highest level at two days after parturition in all the groups. The FSH concentration decreased on day 20 and 45 of gestation and was lowest at two days after parturition in all the groups. The plasma cortisol reached peak level at expected date of parturition but decreased drastically to its lowest level 2 days after parturition. The study reveled that different housing system did not had any significant effect on the blood hormonal profiles during different stages of gestation.